ETR 300 : Oryza Sativa Enterprise Supplier Of Rice & Gas / Siti Khadijah Mohamed Daud ... [et al.] - Mohamed Daud, Siti Khadijah; Osman, Suzzana; Omar Zuhdi, Nasibah; Abdul Hamid, Rahimah; Che Johari, Azzuana (2002)
ORYZA SATIVA. That is our company's name where as refer to it, it clearly mentions as a wholesaler of rice and gas business. The address is at; No, BA, Lorong 24, Taman Patani Jaya, 08000 Sungai Petani, Kedah Darulaman. Generally, we decide to choose Sungai Petani as our location because we find that our factory is located in a strategic site because the number of population is higher with number of 304500 of people. Here we can achieve our target market by supply our product to many place likes restaurant, hotel, canteen, grocery shop and hospital. Other than that, the rent is quite cheap and also far from the hustle and bustle of the city. According to our plan, we are going to run the business on January 1, 2004. The business is categorized as product and services business. We will provide the full range of services and product needed to make our customers satisfied with our business. For our administration and operational department, we have decided to rent a double storey building, which consists of the office (upstairs) and the storage (downstairs). We also did a renovation In order to create a good working environment and also a nice atmosphere for our customers.